Hydrophobic MAO/FSG coating based TENG for self-healable energy harvesting and self-powered cathodic protection - Liu, YuPeng; Sun, WeiXiang; Li, TingHua; Wang, DaoAi (Science China. Technological sciences, 2022)
An organic/inorganic hybrid coating with self-healable hydrophobicity is prepared as triboelectrical layer by micro-arc oxidation (MAO) and fluorinated sol-gel (FSG) coating. The MAO/FSG hybrid coating-based TENG (MF-TENG) has a current output of 31 µA and voltage output of 870 V, which is eight times that of the MAO based TENG. Compared with organic coating, the organic/inorganic hybrid coating has good wear resistance. When the fluorine composition on the surface of the coating is damaged, the self-healing hydrophobicity and electrical output are achieved by transferring loaded perfluorosilane to the damaged surface. The fluorinated sol-gel coating is hydrophobic, which ensures that the coating has good corrosion resistance. Also, the electricity generated in triboelectrification could improve the anti-corrosion performance by cathodic protection. Based on the anti-corrosion, anti-wear and self-healing properties, the MF-TENG has potential applicability in the field of energy collection, energy supply, and corrosion protection.